2006
DOI: 10.1029/2006wr004886
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mass discharge from dense nonaqueous phase liquid source zones using upscaled mass transfer coefficients: An evaluation using multiphase numerical simulations

Abstract: [1] Difficulties associated with identifying the dense nonaqueous phase liquid (DNAPL) source zone architecture at the field scale, combined with the computational costs of field-scale DNAPL dissolution simulations, have motivated the development of a number of simplified models that rely upon upscaled (i.e., domain-averaged) mass transfer coefficients to approximate field-scale dissolution processes. While conceptually attractive, these upscaled models have yet to be fully evaluated for prediction of mass rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(148 citation statements)
references
References 63 publications
6
141
1
Order By: Relevance
“…Geometry of the contaminant source is now being recognized as an important factor impacting the fate of NAPLs in the subsurface [25][26][27][28]. The geometry of the NAPL dictates the surface area, which in turn drives dissolution rates as well as the available area for microbial colonization [3,29].…”
Section: Role Of Geometry In 'Fate and Persistence'mentioning
confidence: 99%
“…Geometry of the contaminant source is now being recognized as an important factor impacting the fate of NAPLs in the subsurface [25][26][27][28]. The geometry of the NAPL dictates the surface area, which in turn drives dissolution rates as well as the available area for microbial colonization [3,29].…”
Section: Role Of Geometry In 'Fate and Persistence'mentioning
confidence: 99%
“…Under previous SERDP sponsorship, Christ et al (2006) developed an upscaled model that uses two site specific parameters: initial average concentration (C o ) and GTP ratio, to quantify the approximate evolution of the contaminant plume as DNAPL dissolves. The DNAPL source zone simulations employed in their study were generated using the SGS-based simulations conditioned to the Bachman Road site (Lemke and Abriola, 2003;2006;Lemke et al, 2004).…”
Section: Ii42 Upscaled Models For Mass Depletionmentioning
confidence: 99%
“…(2006), developed a simplified screening model based upon this metric that successfully captured the relationship between source zone mass removal and down-gradient contaminant flux reduction for a variety of field-scale numerical simulation scenarios. Although this and similar upscaled models may reproduce the general decline in flux-averaged concentrations with mass removal (e.g., Parker and Park, 2004;Christ et al, 2006;Fure et al, 2006;Zhang et al, 2008), they fail to capture the distinct 'multistage' concentration behavior observed as the SZA transforms from ganglia-to pool dominance (see, for example, Lemke et al, 2004b;Parker and Park, 2004;Brusseau et al, 2007Brusseau et al, , 2008Suchomel and Pennell, 2006;Zhang et al, 2008).…”
Section: Ii41 Introductionmentioning
confidence: 99%
See 2 more Smart Citations